1979
DOI: 10.3758/bf03209686
|View full text |Cite
|
Sign up to set email alerts
|

Persistent effect of noise on the acoustic startle reflex in the rat

Abstract: Continuous noise facilitates acoustic startle reflexes in the rat. Rats were exposed to noise for 23 h (Experiment 1) or to 23 h of startle eliciting stimuli at the rate of lImin (Experiment 2). Facilitation was reduced following habituation in Experiment 2, but was unaffected by prolonged noise exposure in Experiment 1. Reflex inhibition produced by a brief noise was not altered by habituation. Prior experiments show that increases in intensity of continuous noise engage two disparate processes which affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…A third possibility is that the background noise could summate with the startle-eliciting stimulus, thus increasing startle. This hypothesis is supported by animal studies (e.g., Cory & Ison, 1979;Hoffman & Fleshler, 1963). Finally, background noise could decrease the signal-to-noise ratio between an acoustic startle-eliciting stimulus and background noise, thus decreasing startle amplitudes.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…A third possibility is that the background noise could summate with the startle-eliciting stimulus, thus increasing startle. This hypothesis is supported by animal studies (e.g., Cory & Ison, 1979;Hoffman & Fleshler, 1963). Finally, background noise could decrease the signal-to-noise ratio between an acoustic startle-eliciting stimulus and background noise, thus decreasing startle amplitudes.…”
Section: Methodsmentioning
confidence: 64%
“…However, the effect of continuous background noise on human startle has, to our knowledge, not been investigated. Animal studies have found that 70‐dB (Cory & Ison, 1979) and 85 dB (Hoffman & Fleshler, 1963) continuous background noise facilitate acoustic startle by up to 100%, compared to ambient background noise. Other studies (e.g., Davis, 1974; Ison & Russo, 1990) did not include an ambient noise level baseline, but found that increases in background noise levels initially increased startle responses followed by a decrease in startle at higher intensities.…”
mentioning
confidence: 99%
“…The mean fiber number was insignificantly different after CHL; however, the mean fiber length and mean fiber density for the lateral lemniscus after CHL was significantly decreased compared to before (t-test: t = 2.548, df = 30, p = 0.0162 and t = 2.388, df = 30, and p = 0.0234, respectively). reflex inhibition produced by brief noise exposure (Cory and Ison, 1979;Wu et al, 1984), indicating in the rat a priming or sensitization effect. It is interesting to note, an increased sensitivity to continuous noise results in suppression in the acoustic startle response (ASR) in rats (Rybalko et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Davis, Svensson, and Aghajanian (1975), for example, reported that d-and I-amphetamine enhance the reflex sensitizing effects of eliciting stimulus repetition without changing sensitization produced by background white noise. Hoffman, Marsh, and Stein (1969) and Cory and Ison (1979) showed that the latter kind of sensitization persists for durations of background noise exposure of up to 24 h. Together, these various demonstrations suggest caution in assuming that all sources of sensitization or response enhancement reflect the same underlying process.…”
Section: Discussionmentioning
confidence: 96%